Transitioning to Good Health and Well-Being - Flahault, Antoine (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
At this purpose characterization, production, effectiveness, safety and use of natural fibers, block copolymeric nanoparticles and food packaging will be briefly described and discussed.